2007
DOI: 10.1007/s10722-006-9125-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of Omani wheat revealed by microsatellites: II. Hexaploid landraces

Abstract: For millennia, wheat (Triticum spp.) has been grown in traditional aflaj-irrigation systems of remote mountain oases in Oman. However, little is known about the diversity of the ancient landraces used. Given recent reports about the occurrence of novel germplasm in such material, the objective of this study was to evaluate the genetic diversity of hexaploid wheat (Triticum aestivum L.) landraces in relation to their geographic origin using microsatellites. The collection covered most of the cultivation areas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
(49 reference statements)
4
19
1
Order By: Relevance
“…Although SSR or microsatellite markers are often of multi-allelic nature, co-dominant inheritance, relative abundance, and extensive genome coverage were observed (Gupta & Varshney, 2000). Microsatellite markers are useful and becoming popular for different applications in wheat breeding due to their high level of polymorphism and easy handling (Devos et al, 1995;Roder et al, 1995;Bryan et al, 1997;Roy et al, 1999;Lelley et al, 2000) and are used to evaluate genetic diversity of hexaploid wheat (Al Khanjari et al, 2007). In the present study SSR markers almost succeeded in discrimination wheat cultivars.…”
Section: Cluster Analysismentioning
confidence: 67%
“…Although SSR or microsatellite markers are often of multi-allelic nature, co-dominant inheritance, relative abundance, and extensive genome coverage were observed (Gupta & Varshney, 2000). Microsatellite markers are useful and becoming popular for different applications in wheat breeding due to their high level of polymorphism and easy handling (Devos et al, 1995;Roder et al, 1995;Bryan et al, 1997;Roy et al, 1999;Lelley et al, 2000) and are used to evaluate genetic diversity of hexaploid wheat (Al Khanjari et al, 2007). In the present study SSR markers almost succeeded in discrimination wheat cultivars.…”
Section: Cluster Analysismentioning
confidence: 67%
“…On the other hand, Al-Khanjari et al (2007) found that all local varieties of wheat from the same geographical area clustered in the same group. In our case, we can hypothesize that the genetic proximity of the cultivars based on their geographical origin results from a local selection and diversification, coupled with weak or nonexistent exchanges of seeds between regions, inducing a geographical structuration and a form of isolation by distance.…”
Section: Genetic Relationship Between Wheat Cultivarsmentioning
confidence: 93%
“…Other than these properties, genetic diversity studies of diverse accessions is strengthen by the advancement and thriving appliance of various types of molecular markers (Khan et al, 2014). For more than two decades, simple sequence repeats (SSRs) or microsatellite markers (Tautz et al, 1986) have been progressively used for diversity analysis of native and contemporary cultivars (Todorovska et al, 2005;Al Khanjari et al, 2007;Colomba and Gregorini, 2011) and has shown promising polymorphism.…”
Section: Detection Of Microsatellitesmentioning
confidence: 99%